Establishing a Green Charcoal Value Chain in Rwanda : A Feasibility Study - World Bank (Washington, DC, 2014)
Biomass is the most important source of energy in Rwanda, especially for domestic cooking. Today approximately 86 percent of primary energy comes from biomass, mainly in the form of wood that is either used directly as a fuel (57 percent), or converted into charcoal (23 percent) together with smaller amounts of crop residues, and peat (6 percent). In the past, the production of charcoal in Rwanda was one of the factors that contributed to deforestation. Nowadays, due to massive reforestation in the country, Rwanda may well be among the few African countries where the relation between charcoal and deforestation no longer exists. However, even with charcoal featuring as an important economic and ecological potential, the sector is generally not considered as a possible means to achieve long-term sustainable development, for example as a low-carbon growth option contributing to energy security and poverty alleviation. In this context, the feasibility study focuses on the elaboration of a road map to develop a modern and efficient charcoal value chain. The economic development and poverty reduction strategy (EDPRS) is the medium term programmatic framework for achieving the country's long term development aspirations as embodied in Rwanda vision 2020, as well as the intermediate targets in the 2015 millennium development goals (MDGs). The modernization of the charcoal sector requires a consensual vision statement from all relevant government authorities on accepting and promoting sustainable charcoal production and utilization.